Impact of working capital management on efficiency of IT sector in India - Manushri Meena (International Journal of Advanced Science and Technology, 2020)
This research work is conducted to analyse the impact of working capital management on profitability of Information technology sector in India. Shareholders’ funds, operating expenses of non-financial firm, total assets and total income have been taken as variables to achieve objective of my study. For conducting this study secondary data was retrieved from Prowess Database of CMIE for ten year period from 2009-10 to 2019-2020 for various IT companies listed on National Stock Exchange of India or Bombay stock exchange. In order to test the relationship between working capital management and profitability, Data Envelopment Analysis (DEA) and Panel data regression analysis of time series and cross-section data has been applied along with correlation analysis. The previous researches have suggested that there is a huge impact of working capital management on the profitability of a firm as it plays an important role in financial decision making for the firm. Thus managers should lay more attention on efficient working capital management so that firms can increase their profits and firm value can be enhanced.